Logo sebagai Media Komunikasi Teknologi Analisis Semiotika pada Logo Meta - Bayu Aji Pamungkas; Anak Agung Gde Agung Indrawan (Universitas Bumigora, 2021)
The Meta logo as a social media company icon has its own uniqueness, namely a two-dimensional and three-dimensional format in one object that seems to move. The Meta logo becomes an interesting object to be studied in a semiotic manner because it is an indirect communication medium. This study uses interpretive qualitative methods by utilizing data collection techniques through documentation, and data analysis through visual and semiotic analysis. The result is that the Meta logo applies several design elements, namely elements of color, line, shape, and chroma. This logo has an implicit meaning in some of its elements. The conclusion is that denotatively the Meta logo still uses the initial color element, namely blue as its trademark. In the line element, this logo is formed from two types of lines, namely straight lines formed diagonally and curved lines. The interesting thing about this Meta logo is the application of shape elements that are symbolic, numbers, and alphabetical. The chroma contained in the color of this logo is formed from the same two-color pigments with different lighting intensities, namely the intensity of the strong blue color and the intensity of the weak blue color. Connotatively, the Meta logo means calm, trust, loyalty, communication, technology, firmness, flexibility, and sustainability.